HUBUNGAN PENGGUNAAN POWERPOINT DENGAN AKTIVITAS DAN HASIL BELAJAR SENI RUPA SMA PGRI 1 PADANG - RINNY IRAWAN, Drs. Eswendi, M.Pd, Drs. Abd. Hafiz, M.Pd (Universitas Negeri Padang, 2013)
The purpose of this research is to describe the correlation beween using powerpoint as learning media with activities and the result of fine art study of the Senior High School students in SMA PGRI 1 Padang. The datas of the study are result of research which are taken after teacher explain the lesson by using powerpoint and questionniare which are filled by students or samples. The sources of data in this research are primary datas that are collected from the students directly through questionare and secondary data in the form of students learning result. The data of 3 learning media powerpoint and students learning activities are taken through questionare and students learning result are taken through teacher‟s evaluation. The result of the study finds that there are correlation between using powerpoint as learning media with learning activity r arithmetic(0,671)> r table (0,159) therefore the hypothesis accepted, for correlation between using learning media power point with students learning result r arithmetic( ) > r table (0,159) the hypothesis accepted, and for correlation between students learning activities point with students learning result r arithmetic( ) > r table (0,159) the hypothesis accepted. Key words: power point, learning activities, result of study.